ANALISIS VEGETASI RIPARIAN SUNGAI WANGGU PADA DAS WANGGU KOTA KENDARI DENGANPENDEKATAN SPASIAL - Hasddin Hasddin (Yayasan Akrab Pekanbaru, 2019)
This study aims to analyze distribution and extent of riparian vegetation of Wanggu DAS in Kendari City area as well as the diversity of riparian vegetation in the Wanggu District of Kendari City. This research was conducted in Wanggu Wanggu Watershed in Kendari City area. The study used qualitative descriptive analysis with ArcGis 10.1 application. The results conclude that; (1) the area of ​​riparian vegetation of Wanggu watershed in Kendari area as a whole is about 132,04 ha with a river length of about 13,722.43 m (13 Km). The area of ​​riparian vegetation is spread over the entire watershed with the widest area in the downstream area of ​​69.81 ha, upstream area 33,34 ha, and middle area 28,86 ha; and (2)riparian vegetation in the Wanggu watershed overall is 25 types consisting of 18 secondary forest species,and 7 types of mangrove forest vegetation (swamp).